The Effects of Health Education on HIV through Audio Visual Media on HIV Prevention Behavior among Adolescents in a High School in Tangerang - Silvia Putri Angelica; Rita Ismail; Desmawati; Lina Ayu Marcelina (Fakultas Keperawatan Universitas Andalas, 2025)
Adolescents are a group at risk of HIV exposure. At this age, adolescents have a high curiosity, so if it is not followed by an attitude that cares about HIV prevention efforts, then the attitude will lead adolescents to behave at risk of HIV, such as premarital sex and injecting drug use. One preventive method that can be taken is to provide education through audio-visual media. This media can help improve learning outcomes and motivation. This study aims to analyze the impact of health education about HIV through audio-visual media on HIV prevention behavior among adolescents in a high school in Tangerang Regency. The study method was quantitative with a quasi-experimental design using one group pre-post design. Instrument of the study was Sexual Behavioral Abstinence and Avoidance of High-Risk Situation Questionnaire (SBAHAQ). Respondents were selected using purposive sampling. The respondents watched audio-visual media (6:50 minutes) about HIV prevention. The pre-test was conducted before the intervention and the post-test was conducted 21 days after the intervention. The total number of respondents was 59 and age ranged between 15 and 18 years. The average score of HIV prevention behavior increased from 11.03 to 13.27 after the intervention with p value 0,001. Health education delivered through audio-visual media about HIV prevention can improve prevention behavior among adolescents in a high school in Tangerang Regency. Audio-visual media can be used in school learning, to make it easier for adolescents to understand HIV prevention behavior and an audio-visual media can be used to increase adolescent behavior in prevention HIV.